2020
DOI: 10.1112/topo.12150
|View full text |Cite
|
Sign up to set email alerts
|

Relations in bounded cohomology

Abstract: We explain some interesting relations in the degree 3 bounded cohomology of surface groups. Specifically, we show that if two faithful Kleinian surface group representations are quasi‐isometric, then their bounded fundamental classes are the same in bounded cohomology. This is novel in the setting that one end is degenerate, while the other end is geometrically finite. We also show that a difference of two singly degenerate classes with bounded geometry is boundedly cohomologous to a doubly degenerate class, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Moreover, the second author also showed that the rigidity holds for complex and quaternionic lattices [Sav20]). The interest in the study of volume of representations has recently grown, leading to the development of a rich literature [Poz15], [KK16], [Tho18], [Far], [Far20].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Moreover, the second author also showed that the rigidity holds for complex and quaternionic lattices [Sav20]). The interest in the study of volume of representations has recently grown, leading to the development of a rich literature [Poz15], [KK16], [Tho18], [Far], [Far20].…”
Section: Historical Backgroundmentioning
confidence: 99%